Rethinking Strength: Black Women's Perceptions of the "Strong Black Woman" Role. (December 2016) - Nelson, Tamara; Cardemil, Esteban V.; Adeoye, Camille T.
In this qualitative study, we examined perceptions of the strong Black woman (SBW) or superwoman role in a sample of 30 Black women. We found that participants conceptualized the SBW/superwoman role through five characteristics: independent, taking care of family and others, hardworking and high achieving, overcoming adversity, and emotionally contained. Most participants were ambivalent about their relationship with this role, given historical accounts and familial examples of Black women. Many participants appropriated the SBW/superwoman role by redefining it in ways that were more empowering and freeing. Several participants were critical of and rejected the SBW/superwoman role, focusing on its problematic and rigid view of strength. All of these perspectives underscore the importance of increasing awareness of restrictive gendered and racialized role expectations as well as the desire to maintain connections to the cultural legacy of Black women. Several important contextual factors (e.g., social status, family relationships) emerged that are relevant to the identified themes. Results from this study highlight how the discourse of strength and familiarity with the SBW/superwoman role are pervasive among Black women. Our findings underscore the need for practitioners to understand the complexity in how Black women make meaning of this role relative to help seeking for physical and mental health. Online slides for instructors who want to use this article for teaching are available on PWQ 's website athttp://pwq.sagepub.com/supplemental